Teori Keadilan John Rawls dan Relevansinya dalam Formulasi Kebijakan Pembagian Harta Bersama di Era Kontemporer: Teori Keadilan John Rawls dan Relevansinya dalam Formulasi Kebijakan Pembagian Harta Bersama di Era Kontemporer - Sulaiman, Heri; Marwati, Lusi; Alfarezi, Salman; Sulistiowati, Tri; Machmud , Aris (Yapilin Press, 2025)
The problem of justice in the division of joint property after divorce has become increasingly complex in the contemporary era, along with social, economic, and legal changes. This article discusses John Rawls' theory of justice, especially the principle of justice as fairness, and its relevance in formulating joint property division policies. The purpose of this study is to examine the extent to which Rawls' theory can provide a normative framework in assessing and improving joint property division policies to be more equitable. The method used is qualitative research with a juridical-philosophical approach, through literature analysis of Rawls' works and positive legal regulations in force in several countries, including Indonesia. The research findings show that Rawls' principles of justice, especially the difference principle and the principle of equal freedom, can be used to build a joint property division system that pays attention to the balance between individual rights and protection of economically vulnerable parties. In conclusion, the formulation of joint property division policies based on Rawls' theory will encourage the creation of a legal system that is not only legalistic, but also guarantees substantive justice for both parties. Therefore, the integration of Rawlsian justice values ​​in legislation is very relevant to answer the challenges of justice in the dynamics of contemporary society.